The Law and Society Reader II - Erik Larson, Patrick Schmidt (NYU Press, 2014)
Many students find themselves drawn to law as a topic or field of study. They often see in law an ability to right injustices, perceiving in law the advantages of independence, logic, and structure, which combine to promise the â€œcorrectâ€ outcomes. From this perspective, law appears as a sanctuary from the dirtiness of politics, the ambiguity of culture, the self-interest of economics, and the messiness of social relations. The kind of legal education provided in many countries has done little to discourage students from their belief that law rises above these potential contaminants and remains pure. We may be a long way removed from the view that the laws of a nation are the expression of the will of a divine creator, but for many the appeal to law remains rooted in the belief of the distinctiveness of law as a pursuit. If anything, from this perspective, the study of political, cultural, economic, and social processes is most useful for how it can illuminate the problems that law should address. Indeed, a century ago, many reformersâ€”the legal realistsâ€”turned to social science as one way of giving law exactly that sense of direction. Over the 20th century, however, the social sciences evolved and legal scholars changed their approach. Careful empirical research and new veins of theoretical insight complicated our understanding of law in the hands of people. Law, all but the most resolute will concede, is not as independent as once envisioned. As law actually operates, it remains connected to the messiness of the daily life of politics, culture, economic activity, and social relations. The belief that law is somehow majestically separate and uniquely powerful still influences the rhetoric of law and, through that rhetoric, aspects of how the law works in action. There is drama in the portrayal of law in fictional entertainment and in media reports of factual cases. But when we tear off the veneer of appearances, we open up a world that needs and welcomes any disciplinary or interdisciplinary approach that can help us understand how law works in society This research tradition of social science concerned with law has long been a recognized field of scholarly inquiry, although it has been formally organized for only about half of a century. Founded in 1964, the Law and Society Association serves as a scholarly community for people from diverse disciplinary backgrounds who seek to bring their intellectual perspectives to the study of law. As an interdisciplinary community, the Law and Society Association draws together legal scholars, social scientists of all stripes (including sociologists, political scientists, anthropologists, psychologists, linguists, and economists), and humanists (notably historians, philosophers, and scholars of literature).